DEVELOPING STUDENTS' CLINICAL SKILLS BASED ON INNOVATIVE PEDAGOGICAL APPROACHES IN MEDICAL EDUCATION - Mahsudov Valijon Gafurjonovich, (TADQIQOTLAR, 2026)
Abstract.  This  article  analyzes  the  issues  of  forming  students'  clinical  skills based on innovative pedagogical approaches in the medical education system. It is argued  that  the  introduction  of  modern  educational  technologies,  in  particular, simulation  learning,  problem-based  learning  (PBL),  case-study  and  interactive methods  into  the  educational  process  serves  to  integrate  students'  theoretical knowledge  with  practice.  It  is  also  shown  that  through  these  approaches,  students acquire the skills of clinical thinking, diagnosis, correct decision-making and effective communication with the patient. The results of the study confirm the importance of innovative pedagogical methods in improving the quality of medical education and training competitive, highly qualified specialists.